Evaluation of microleakage in Class II composite restorations: Bonded-base and bulk-fill techniques - Atiyeh Feiz; Marzieh Sajedi; Niloufar Jafari; Edward J. Swift (Wolters Kluwer Medknow Publications, 2021)
Background: This study compared microleakage of Class II cavities restored using bonded-base and bulk-fill techniques with different bases.Materials and Methods: In this in vitro study, in 60 extracted human molars, standardized (4 mm × 2 mm × 8 mm) Class II cavities were prepared, such that the gingival floor was located 1 mm below the CEJ. The teeth were randomly divided into five groups and filled with: (1) Fuji II LC + x-tra fil, (2) Ionoseal + x-tra fil, (3) x-tra base + x-tra fil, (4) Grandio Flow + x-tra fil, and (5) x-tra fil only [control group]; in open-sandwich technique, the base thickness was 1 mm. The bases were coated all gingival floor. Except for the first group, where dentin conditioner was used, the Clearfil SE bond was applied before application of the bases and restorative materials as a bonding agent. After 500 thermocycles between 5°C and 55°C, the specimens were immersed in 0.5% basic fuchsine solution for 24 h. The restored teeth were sectioned, and the dye penetration in gingival floor was observed by a stereomicroscope at ×32. The data were analyzed using Kruskal-Wallis and Mann-Whitney tests in SPSS software. The significance was determined at 0.05 confidence interval.Results: The statistical analysis revealed a significant difference in microleakage among the study groups (P < 0.001). The Ionoseal group followed by the control group (x-tra fil composite) had the greatest microleakage. Except for the Ionoseal group, all other groups had significantly less microleakage than the control group.Conclusion: The use of bonded-base techniques could reduce microleakage, including those in bulk-fill composite restorations.